Dataset: Distribution and tree cover of the Moroccan fir (Abies marocana Trab.) in Talassemtane National Park (Western Rif, northern Morocco) - Gutiérrez Hernández, Oliver (Universidad de Málaga, 2025)
This dataset contains polygon features representing the distribution and tree cover of the Moroccan fir (Abies marocana Trab.) within Talassemtane National Park, located in the Western Rif of northern Morocco. The dataset includes 144 MultiPolygon records classified into four forest structural categories: pure stands, mixed stands dominated by A. marocana, mixed stands with secondary A. marocana, and areas with scattered individuals. Two main forest zones are distinguished: Talassemtane forest and Tazaot forest, corresponding to the species’ primary distribution nuclei within the park. The physiognomic–structural classification identified 4,206 hectares of A. marocana formations. Pure stands represent 1,648 ha (39.2%), followed by mixed stands with secondary presence (1,385 ha; 32.9%). Mixed stands with dominant presence cover 802 ha (19.1%), while marginal or scattered occurrences occupy 371 ha (8.8%). All area calculations are expressed in hectares, and the dataset is fully referenced in EPSG:32630 (WGS 84 / UTM zone 30N). Aerial imagery from Airbus Pléiades (50 cm resolution) was used to delineate and classify forest patches, supported by auxiliary information. Digitisation, geoprocessing, mask tasks, and mapping workflows were carried out in the ArcGIS Pro 3.5 environment. The dataset is provided in both GeoPackage (.gpkg) and Shapefile (.shp) formats to ensure broad compatibility with GIS platforms. It is intended for use in ecological research, conservation planning, forest structure assessment, and landscape-level analysis within protected mountain ecosystems.
Keywords: Abetos - Mediterráneo (Región); Abetos - Distribución geográfica; Fitogeografía; Biogeografía; Abetos españoles - Distribución geográfica; Ecosistemas mediterráneos; Reservas de la biosfera; Abies marocana; Moroccan fir; Talassemtane National Park; Abies pinsapo; Baetic-Rifan fir; IUCN Red List; Intercontinental Biosphere Reserve of the Mediterranean; Circum-Mediterranean firs